Implementasi manajemen strategi dalam penguatan daya saing koperasi syariah di era ekonomi digital: Studi kasus pada KSPPS BMT UGT Sidogiri - Putri, Dieva Rullyeza Chelsealia (Maliki Interdisciplinary Journal, 2025)
This study aims to analyze the implementation of strategic management in enhancing the competitiveness of Islamic cooperatives in the digital economy era, focusing on the case of KSPPS BMT UGT Sidogiri. As a microfinance institution, Islamic cooperatives play a vital role in empowering communities based on justice and Islamic principles. This research employs a descriptive qualitative method using a library research approach, in which all data were obtained from academic literature, journals, books, and institutional reports. The findings indicate that strategies involving human resource development, digital transformation, institutional partnerships, and Sharia-based governance significantly strengthen the competitiveness of cooperatives. KSPPS BMT UGT Sidogiri exemplifies a balanced implementation of strategic management between economic and spiritual values, enabling sustainability amid the expansion of digital financial institutions.